Analisis Kemampuan Representasi Matematis Siswa dengan Model Group Investigation Pada Materi Turunan - Putri Sucita Sari; Nindy Citroresmi Prihatiningtyas; Citra Utami (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2020)
Abstract:The mathematical representation ability of students at a Senior High School in Singkawang is still low. This is due to the habit of students receiving direct learning and passive activities. This article tries to find out the differences in mathematical representation abilities between students who are given the Group Investigation (GI) learning model and students who are given the direct learning model and describe the mathematical representation abilities of students in terms of learning activities with the GI learning model. The results showed that there were differences in the increase in the mathematical representation ability of students who were given the GI learning model and those who were given the direct learning model. The active mathematical representation ability of students is in the high category, while students with moderate and passive activities have moderate representation skills. Abstrak:Kemampuan representasi matematis siswa di salah satu SMA Negeri di Singkawang masih rendah. Hal ini dikarenakan kebiasaan siswa menerima pembelajaran langsung dan aktivitas yang pasif. Artikel ini mencoba mengetahui perbedaan kemampuan representasi matematis antara siswa yang diberikan model pembelajaran Group Investigation (GI) dengan siswa yang diberikan model pembelajaran langsung serta mendeskripsikan kemampuan representasi matematis siswa ditinjau dari aktivitas belajar dengan model pembelajaran GI. Hasil penelitian menunjukkan terdapat perbedaan peningkatan kemampuan representasi matematis siswa yang diberikan model pembelajaran GI dengan siswa yang diberikan model pembelajaran langsung. Kemampuan representasi matematis siswa yang aktif berada pada kategori tinggi, sedangkan siswa degan aktivitas sedang dan pasif memiliki kemampuan representasi sedang.